1990
DOI: 10.1038/ki.1990.293
|View full text |Cite
|
Sign up to set email alerts
|

Soft tissue calcification in pediatric patients with end-stage renal disease

Abstract: Soft tissue calcification is a recognized complication of uremia in adult patients and has been implicated as a cause of ischemic necrosis, cardiac arrhythmias, and respiratory failure. However, soft tissue calcification has been regarded as rare in pediatric renal patients. Following a sudden death due to pulmonary calcinosis in an adolescent after renal transplantation, we retrospectively reviewed clinical, biochemical and autopsy data of 120 patients with uremia, on dialysis, or following renal transplantat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
158
1
3

Year Published

1992
1992
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 276 publications
(166 citation statements)
references
References 17 publications
4
158
1
3
Order By: Relevance
“…Although the prescribed dosage of vitamin D is also a surrogate marker of the severity of hyperparathyroidism, the vitamin D dosage predicted vascular damage independent of iPTH levels. The role of vitamin D in the pathogenesis of vascular calcification has been shown in other observational studies 4,5 as well as in ex vivo 34 and in vitro models. 35 Although the primary role of vitamin D is to increase the gastrointestinal absorption of calcium, it also significantly increases PO 4 absorption.…”
Section: Discussionmentioning
confidence: 65%
“…Although the prescribed dosage of vitamin D is also a surrogate marker of the severity of hyperparathyroidism, the vitamin D dosage predicted vascular damage independent of iPTH levels. The role of vitamin D in the pathogenesis of vascular calcification has been shown in other observational studies 4,5 as well as in ex vivo 34 and in vitro models. 35 Although the primary role of vitamin D is to increase the gastrointestinal absorption of calcium, it also significantly increases PO 4 absorption.…”
Section: Discussionmentioning
confidence: 65%
“…28 They are often considered a consequence of an increased calcium phosphate product, in association with secondary hyperparathyroidism or adynamic bone disease. 29 On the other hand, diabetes is known to be frequently associated with ESRD. 30 Diabetic patients with advanced renal failure have a mediocre vascular prognosis, related in particular to macroangiopathies and increased arterial stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…Rats that were treated with high-dose vitamin D developed calcification in the aorta, carotid, hepatic, mesenteric, renal, and femoral arteries (26). Clinical studies have also reported an association between vascular calcification and use of vitamin D therapy in hyperphosphatemic patients with renal failure (27,28). Vascular smooth muscle cells (VSMC) have been shown to express vitamin D receptors (29).…”
Section: Control Of Secondary Hyperparathyroidism: Vitamin D Versus Cmentioning
confidence: 99%